ON INDIVIDUAL DIFFERENCES IN HUMAN BLOOD - Karl Landsteiner; Philip Levine (1928)
A clear-cut differentiation of human blood, aside from the blood groups, could be made by means of special agglutinating immune sera. The observations point to the existence of several agglutinable factors for which no agglutinins are demonstrable in normal human sera. In view of the latter circumstance the results reported do not imply any change in the scheme of the four blood groups. The body of serological evidence leads to the inference of a high degree of biochemical differentiation among individuals.